The Influence of Consumer Perceptions on Product Attributes towards Brand Preferences of Alpina Outdoor Sport and Eiger Adventure - Mochamad Alem Diamanta Kurnia; Irsanti Hasyim (International Journal of Entrepreneurship, Business, and Creative Economy, 2023)
Alpina and Eiger are outdoor product pioneers in Indonesia. Initially, Alpina dominated the Indonesian outdoor product market, but it was unable to compete with Eiger. According to the preliminary research findings, more than 50% of respondents claimed that they prefer to buy outdoor products from Eiger over Alpina because Eiger products are superior in terms of product quality, product features, and product style & design. In this study, the independent variables are product attribute variables (product quality, product characteristics, and product style & design), and the dependent variable is brand preference. Data was gathered through interviews, observations, literature studies, and questionnaires completed by 120 people using the judgement sampling approach. Multiple linear regression study results reveal that product attribute dimensions have a positive and significant influence on brand preference simultaneously. According to the coefficient of determination calculation results, the independent variable contributes 45.1% to the dependent variable.